Differential regulation of IL-23 production in M1 macrophages by TIR8/SIGIRR through TLR4- or TLR7/8-mediated signaling. (November 2017) - Yamaguchi, Rui; Sakamoto, Arisa; Yamamoto, Takatoshi; Narahara, Shinji; Sugiuchi, Hiroyuki; Yamaguchi, Yasuo
Highlights: SIGIRR is a negative regulator of TLR4 signaling. SIGIRR is a positive regulator of TLR7/8 signaling. SIGIRR deficiency promotes IRF4 expression. SIGIRR deficiency modulates IL-23 expression via IRF4. Abstract: Cross-talks between toll-like receptors (TLRs) including various negative regulatory mechanisms are many unknown. We investigated the differential mechanism of IL-23 production in M1 macrophages by single immunoglobulin interleukin-1 receptor-related (SIGIRR) molecule through TLR4 or TLR7/8. IL-12p40 production by M1 macrophages pretreated with human neutrophil elastase (HNE) was synergistically enhanced IL-12p40, but not IL-23 production, after exposure to lipopolysaccharide (LPS). LPS (a TLR4 agonist) induced a slight increase of IL-23 production, while Resiquimod (a TLR7/8 agonist) significantly enhanced IL-23 production. Expression of SIGIRR protein, a negative regulator of TLR4, was higher in M1 macrophages than in monocytes. Interestingly, SIGIRR siRNA induced a slight increment of IL-23 production after exposure of macrophages to LPS, while IL-23 production in response to Resiquimod was significantly upregulated by SIGIRR siRNA. Silencing SIGIRR enhanced IRF4 protein level determined by western blotting or ELISA. IRF4 siRNA dramatically restored IL-23 production after exposure to Resiquimod in macrophages transfected with SIGIRR siRNA. In conclusion, production of IL-23 is differentially regulated in M1 macrophages by SIGIRR through TLR4- or TLR7/8-mediated signaling. SIGIRR is both a negative regulator of TLR4 and a positive regulator of TLR7/8.